A Dynamically Tunable, Bioinspired Micropatterned Surface Regulates Vascular Endothelial and Smooth Muscle Cells Growth at Vascularization. Issue 41 (6th September 2016) - Gong, Tao; Zhao, Kun; Liu, Xian; Lu, Liuxuan; Liu, Dian; Zhou, Shaobing
Abstract : Regulation of the growth of vascular endothelial cells (ECs) and smooth muscle cells (SMCs) with artificial vascular grafts at vascularization is well‐known to regenerate functional blood vessels for treating cardiovascular disease; however, little research has been published on this subject. Here, a novel polymer vascular graft is presented, whose inner surface contains an assembled circular microgroove pattern decorated with a combination of concentric circular microgrooves and radial, straight microgrooves inspired by the orientation of SMCs and ECs in natural tissues. The surface micropatterns can produce dynamically tunable variations via the thermally switched shape memory. The results from the in vitro EC/SMC co‐cultures reveal that the surface micropatterns have a great capacity to regulate the specific distribution of ECs/SMCs because the ECs grow along the radial, straight microgrooves and the SMCs grow along concentric circular microgrooves. The in vivo vascularization is further analyzed by implanting the vascular graft in the rabbit carotid artery. Both histological analysis and immunofluorescence staining demonstrate that it is capable of highly effectively capturing ECs and SMCs in the blood and subsequent regeneration of new blood vessels. Therefore, this study opens a new possibility for regenerating neovessels to replace and repair damaged vessels for cardiovascular diseases treatment. Abstract : A vessel‐induction active biomaterial, which is in form of a smart cell‐free vascular graft with bioinspired micropatterns on its inner surface, is successfully developed. The surface micropatters can produce a thermo‐switched dynamic change and have a great capacity of inducing the formation of a newly functional blood vessel through highly effectively capturing vascular endothelial and smooth muscle cells in blood.